La bioeconomía hacia una productividad sostenible en el sector agrícola de Colombia: análisis desde su implementación en Alemania y España. (2022)
The bioeconomy is known as the biologically based economy that transforms the knowledge of science and biology into new, sustainable and efficient products, which is why the bioeconomy is taken as one of the most important strategies to promote and implement benefits to a country. , because it is a comprehensive development proposal with environmental, social and economic sustainability.